Long-Term Surgical Outcome of Canal-Tympanoplasty in Patients With Schuknecht Type B Congenital Aural Stenosis - Lee, Yoonjae; Park, Moo Kyun; Lee, Jun Ho; Lee, Sang-Yeon; Suh, Myung-Whan (Clinical and experimental otorhinolaryngology, 2025)
Objectives. Congenital aural atresia (CAA) is a complex condition that manifests in various forms, including Schuknecht type B stenosis, which is characterized by a congenitally narrow bony external auditory canal (EAC). This study aims to evaluate the long-term surgical outcomes of canal-tympanoplasty in patients with Schuknecht type B CAA.Methods. The study included 21 ears diagnosed with Schuknecht type B CAA, all of which underwent canal-tympanoplasty. Reconstruction of the large EAC and tympanic membrane involved conchal flap meatoplasty, bony EAC drilling, ossicular reconstruction, and overlay tympanoplasty. Standard pure-tone audiometry was analyzed at multiple post-surgery time points: 3, 6, 12, and 24–60 months. Additionally, the incidence of postoperative complications was assessed.Results. The hearing outcomes of canal-tympanoplasty in this case series were satisfactory. Serviceable hearing was achieved in all patients after 3 months and was maintained in 85% of patients for 1 year. The air-bone gap improved from a preoperative average of 39.3±15.1 dB to 13.7±7.4 dB at 3 months, 16.4±10.5 dB at 6 months, 19.1±11.7 dB at 12 months, and 21.5±16.1 dB at 2–5 years postoperatively. Three patients required revision canal-tympanoplasty due to hearing deterioration, representing 14.3% of the cases. There were no instances of postoperative infection, facial nerve weakness, vertigo, deterioration of bone conduction thresholds, or complete restenosis of the EAC.Conclusion. Canal-tympanoplasty proved to be a satisfactory surgical intervention for patients with Schuknecht type B CAA. This procedure led to significant improvements in hearing outcomes, providing serviceable hearing that lasted for several years. Moreover, the risk of postoperative hearing deterioration and/or the need for revision surgery within 1 year was considered acceptable.